Serum Oxidative Stress and Creatine Kinase Activity Related to Hoffman’s Syndrome - Mohammed, I. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Several symptoms of hypothyroidism characterized by low FT3 and FT4 were classified into hypothyroidism and Hoffman’s syndrome .It was accepted that free radical generation and lipid peroxidation are associated with many diseases. Creatine kinase in serum is affected by thyroid hormones. This study was undertaken to investigate the relationship between malondialdehyde as a general lipid peroxidation marker and CK activity in patients with primary hypothyroidism and Hoffman’s syndrome which indicatees hypothyroidism with undetectable FT3 and FT4 in serum with elevated values of TSH. The study revealed that MDA is within the normal range, while CK activities in sera of Hoffman’s syndrome were increased with many folds compared to that of primary hypothyroidism and control values.